2018
DOI: 10.1371/journal.pone.0199012
|View full text |Cite|
|
Sign up to set email alerts
|

Complex polymorphisms in endocytosis genes suggest alpha-cyclodextrin as a treatment for breast cancer

Abstract: Most breast cancer deaths are caused by metastasis and treatment options beyond radiation and cytotoxic drugs, which have severe side effects, and hormonal treatments, which are or become ineffective for many patients, are urgently needed. This study reanalyzed existing data from three genome-wide association studies (GWAS) using a novel computational biostatistics approach (muGWAS), which had been validated in studies of 600–2000 subjects in epilepsy and autism. MuGWAS jointly analyzes several neighboring sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 163 publications
0
16
0
Order By: Relevance
“…Over the last decades, genome-wide association studies (GWASs) have successfully identified cell adhesion molecules as one of the most prominent group of genes whose expression is altered in melanoma and breast cancer cells ( Akbani et al, 2015 ; Wittkowski et al, 2018 ). Among these genes, integrins stand out because they are the receptors that facilitate adhesion, migration, and invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, genome-wide association studies (GWASs) have successfully identified cell adhesion molecules as one of the most prominent group of genes whose expression is altered in melanoma and breast cancer cells ( Akbani et al, 2015 ; Wittkowski et al, 2018 ). Among these genes, integrins stand out because they are the receptors that facilitate adhesion, migration, and invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) has a high mortality rate, which is largely due to development of metastases (1). The epithelial-to-mesenchymal transition (EMT) serves a central role in metastasis formation, and is thus an important treatment target (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, β-cyclodextrin has been used to treat Niemann-Pick Disease Type C and to promote atherosclerosis regression by releasing trapped cholesterol from lysosomes and normalizing cholesterol levels in the liver [ 21 , 22 , 23 ]. With these properties, HP-β-CD is widely used to deplete cholesterol from cell membranes and lipid rafts, which can affect many signaling pathways [ 24 , 25 ]. Numerous studies have shown that HP-β-CD can inhibit the metastasis of triple-negative breast cancer cells by depleting cholesterol [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…With these properties, HP-β-CD is widely used to deplete cholesterol from cell membranes and lipid rafts, which can affect many signaling pathways [ 24 , 25 ]. Numerous studies have shown that HP-β-CD can inhibit the metastasis of triple-negative breast cancer cells by depleting cholesterol [ 25 , 26 , 27 , 28 ]. In addition, the effect of HP-β-CD on cellular cholesterol has been demonstrated to be closely related to their concentration and the cholesterol content of treated cells [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%